Septoria gynurae Causing Leaf Spot Disease on Crassocephalum crepidioides in Korea - Bora Nam; Joon-Ho Choi; Seong-Jin Lee; Hyeon-Dong Shin; Young-Joon Choi (한국균학회지)
Crassocephalum crepidioides is a flowering plant in the Asteraceae family that is native to tropical Africa but has become a significant weed in several Asian regions, including Korea. In October 2022, angular leaf spots were observed on C. crepidioides that coalesced into larger lesions with visible pycnidial conidiomata and conidial tendrils under moist conditions. Morphological and molecular analyses identified the causative pathogen as Septoria gynurae. This is the first report of S. gynurae and a fungal disease affecting C. crepidioides in Korea. This study provides the first molecular phylogenetic information on this species and reveals its close relationship with other Septoria species that infect Asteraceae. Septoria gynurae is a potential biocontrol agent; however, further studies are needed to confirm its host specificity and broader effects.